Public finance and public policy - Gruber, Jonathan (Worth Publishers, 2007)
The new edition, fully updated with the most recent data and research possible, includes new coverage of the Medicare drug benefit, changes in the tax code, Hurricane Katrina, and the ongoing debate over privatization.